UterUs: Changing the Perception of Menstrual Health on College Campuses - Riddick-Cherry, Imani Devon (East Carolina University, 2023)
UterUs is a non-profit group dedicated to bringing sustainable and accessible, reusable menstrual hygiene products to the Pitt County and ECU communities. Advocating for reusable menstrual products can empower menstruators to explore alternative options and change how future generations think about menstrual hygiene. We have partnered with DotCup & June Cup, reusable menstrual cup companies, to bring menstrual cups to Pitt County and ECU. They offer a ‘buy-one-give-one’ promotion, meaning for every cup purchased, one cup is donated to a community in need. DotCup’s CEO, Betsy Drach, has promised us that they would provide us with the cups to donate to local shelters and organizations that might find a need for them. We believe that menstrual cups could be cost-effective in the long run, ensure that students have the coverage they need, and change the mentality of alternative menstrual products in the future. Given Pitt County’s 24.5% poverty rate compared to North Carolina’s 16.8%, we believe the community has a great need for these cups. We have reached out to local shelters and are making a lot of progress! We are considering reaching out to high schools next. We have also considered the Purple Pantry or the Student Health Center as distribution centers for students in need. UterUS has fundraised and received grants for thousands of dollars to purchase reusable cups and has already given more than 400+ free cups to our community. We have also provided them with other significant menstruation and empowerment resources from other groups at ECU like the Women and Gender Office and in the community like the Greenville Health Department. We have presented our research and lasting impact to ECU’s Research and Creative Achievement Week and Undergraduate Research and Creative Activity Awards and received an award in the Humanities department in 2022 and received $2,000+ to continue our non-profit research in Spring 2022 We will continue to search for funding and people willing to try reusable menstrual products in our community to allow us to keep donating and educating, to create a community of period-positive individuals for years to come in Eastern NC.
Keywords: Menstrual Health; Reusable Cups; Sustainability; Community